Regulatory Roadmap for R&D to Market the New Drugs in India with a Special Emphasis on the NDCT Rule 2019 and the Drug and Cosmetic Act - Jain, Pragati; Srivastava, Abhinav; Verma, Anurag; Saxena, Urvashi (International Journal of Pharmaceutical Investigation, 2026)
The stepwise overview of the regulatory approval pathway for new drugs in India, focusing on requirements and key forms mandated by the NDCT Rules, 2019. It explains how new drugs are legally defined and categorized, setting the stage for regulatory requirements. The process begins with preclinical safety testing, overseen by Animal Ethics Committees, followed by preparation of a detailed dossier and application for a test license (Form 29). Clinical trial approval is sought through the submission of Form CT-04 on the SUGAM portal and ethics committee clearance. The CDSCO and Subject Expert Committees (SEC) review each stage, requesting clarifications if needed. Successful applicants receive authorization via Form CT-06 to begin clinical trials. During these trials, all protocol changes and serious safety events must be reported. Additionally, approval for bioavailability/bioequivalence and clinical trial centers is obtained using forms such as CT 05-07 and CT 08-09. After trial completion, the sponsor submits a comprehensive marketing application (Form CT-21). With a thorough review, final marketing authorization is granted through Form CT-23. The paper highlights post-marketing requirements such as ongoing pharmacovigilance and periodic surveillance, ensuring continued patient safety. It addresses challenges like regulatory delays, ethical safeguards, and global harmonization, while emphasizing the growing role of digitalization and artificial intelligence in improving efficiency and safety monitoring. Practical recommendations for researchers, industry, and regulators are provided to streamline the new drug approval process, safeguard ethical standards, and accelerate patient access to innovative therapies in India.
Keywords: Clinical Trial Forms; India; NDCT Rules 2019; New Drug Approval; Pharmacovigilance; Regulatory affairs.